Tumor‐intrinsic CD21 expression impacts the response of B‐cell malignancy cells to CD19‐CAR‐T cells. Issue 4 (25th March 2022) - Li, Dan; Xu, Qiongyu; Hu, Yutian; Wang, Wenbing; Xie, Shufeng; Zhao, Chunjun; Liu, Han
Abstract: CD19‐chimeric antigen receptor (CAR)‐based T‐cell therapy has produced promising clinical responses in patients with relapsed or refractory B‐cell malignancies. However, a significant portion of patients with mature B cell‐derived malignancies, including chronic lymphocytic leukemia (CLL) and non‐Hodgkin's lymphoma (NHL), do not respond to CD19‐CAR‐T cell therapy. Whether any characteristics and biomarkers intrinsic to cancer cells themselves can predict the CD19‐CAR‐T cell therapeutic response remains largely unknown. Surprisingly, by using experimental models, we show here that malignant B cells bearing CD21, a mature B cell marker, could not be efficiently killed by CD19‐CAR‐T cells. CD19, CD21, and CD81, together with CD225, form the B cell coreceptor complex that enhances B cell‐mediated signaling. Our results indicated that CD21 affected the recognition of CD19‐positive tumor cells by CD19‐CAR‐T cells and impaired the antitumor capacities of these effector cells. We have not only uncovered a mechanism underlying the impairment of CD19‐CAR‐T cells in mature B cell‐derived CLL and NHL, but also proposed a pretreatment biomarker that may predict CD19‐CAR‐T cell therapeutic response, thus preventing foreseeable therapy failure and suggesting optimal personized therapies. Graphical Abstract: Tumor‐intrinsic CD21 impairs the target cell recognition and the cytotoxicity of the CD19‐CAR‐T cells.